Research Mapping of Fisheries Resource Management in Coastal Areas: A Bibliometric Analysis - Nofirman Nofirman; Rani Eka Arini; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis of the literature on government budget efficiency. This bibliometric analysis explores the evolution and integration of themes within fisheries management research from 1959 to 2024. Utilizing VOSviewer for keyword co-occurrence and network visualization, the study identifies dominant themes such as